IBADAH PUASA DAN PEMBENTUKAN KETAKWAAN: ANALISIS QS. AL-BAQARAH AYAT 183 DALAM PERSPEKTIF TAFSIR AL-MISHBAH - Nurafiah Nurafiah; Mukayyat Al-Amin (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2026)
This study examines the concept of worship as a means of building piety in QS. Al-Baqarah verse 183 from the perspective of Tafsir Al-Mishbah. Through hermeneutic analysis of the verse, fasting is described as an act of self-control that directly shapes piety with keywords such as shiyam and liyattaqu. Overall, this study contributes to the study of the Qur'an and its implications for Islamic religious education. The purpose of this study is to analyze the hermeneutic interpretation of the verse in order to deepen the understanding of the spiritual dimension of fasting. The method applied is a literature study with a qualitative hermeneutic approach involving analysis of the main sources of QS. Al-Baqarah verse 183 and Tafsir Al-Mishbah. The results show that fasting in this verse is more than just a ritual, but a way to form relevant piety, with the core themes of spiritual and moral strengthening. In conclusion, this study encourages practical application in da'wah and religious curricula to instill pious character in the contemporary era.